Concentration Gradient‐Based Soft Robotics: Hydrogels Out of Water. (9th September 2020) - López‐Díaz, Antonio; Martín‐Pacheco, Ana; Rodríguez, Antonio M.; Herrero, M. Antonia; Vázquez, Andrés S.; Vázquez, Ester
Abstract: Hydrogels are biocompatible soft materials that resemble biological tissues more than any other material. However, the use of these systems in soft robotics has been limited to aqueous environments. In the work published to date, hydrogels have relied on external water to swell or shrink in response to stimuli and, therefore, to actuate macroscopically. In the work reported here, this limitation is overcome by synthesizing a novel type of electroactive hydrogels capable of actuating when a low electric field is applied, even outside water. The bending actuation of these materials is caused by the movement of solvated ions within the hydrogel, which generates a concentration gradient, making it possible to use them directly in ambient‐air conditions. A mathematical model for this behavior is proposed. Issues like resistive heating and material drying are addressed by preparing graphene hybrid hydrogels and by using hygroscopic salts. Two applications are presented as a demonstration of the capabilities of these hydrogels: a soft gripper with two continuum actuators and a soft fingertip capable of changing its volume and stiffness. In addition, the possibility of fabrication by 3D printing technologies enhances the applicability of these promising materials, thus paving the way for innovative developments. Abstract : This work presents a new type of electroactive hydrogels capable of actuating outside water. The bending actuation is studied in different media: water, ionic liquid, and air. A mechanism and a mathematical model to explain this behavior are introduced. Finally, a gripper and a soft fingertip are presented as demonstrators, and 3D printing as a manufacturing method.